Daidzein-Decorated Gold Nanoparticles as a Novel Antimicrobial Strategy Against Carbapenem-Resistant Enterobacteriaceae - Pan J; Zhang J; Hu P; Yao Z; Zhang X; Zhou T; Shen M (International Journal of Nanomedicine, 2025)
Juan Pan,1 Jia Zhang,2 Panjie Hu,1 Zhuocheng Yao,1 Xiaotuan Zhang,1,3 Tieli Zhou,1 Mo Shen1 1Department of Clinical Laboratory, The First Affiliated Hospital of Wenzhou Medical University Key Laboratory of Clinical Laboratory Diagnosis and Translational Research of Zhejiang Province, Wenzhou, Zhejiang, 325000, People’s Republic of China; 2School of Laboratory Medicine and Life Science, Wenzhou Medical University, Wenzhou, People’s Republic of China; 3Department of Clinical Laboratory, The Second Affiliated Hospital, Hengyang Medical School, University of South China, Hengyang, People’s Republic of ChinaCorrespondence: Mo Shen, Department of Clinical Laboratory, The First Affiliated Hospital of Wenzhou Medical University, Key Laboratory of Clinical Laboratory Diagnosis and Translational Research of Zhejiang Province, Wenzhou, Zhejiang, 325000, People’s Republic of China, Email shenmo601@163.com Tieli Zhou, Department of Clinical Laboratory, The First Affiliated Hospital of Wenzhou Medical University, Key Laboratory of Clinical Laboratory Diagnosis and Translational Research of Zhejiang Province, Wenzhou, Zhejiang, 325000, People’s Republic of China, Email wyztli@163.comIntroduction: Bacterial resistance to carbapenems is on the rise, and the failure of common antimicrobials poses a serious challenge in treating infections caused by drug-resistant strains. In this scenario, nanomaterials have received widespread attention in medicine.Methods: In this study, the activity of daidzein-decorated gold nanoparticles (Daidzein_Au NPs) against carbapenem-resistant Enterobacteriaceae (CRE) strains was validated via in vivo and in vitro experiments, such as the microdilution broth method, growth curves, time-killing assays, and an abdominal infection model in mice. The potential mechanisms involved were examined using fluorescence quantification of N-phenyl-1-naphthylamine, propidium iodide, and reactive oxygen species (ROS) levels and transcriptomic analysis.Results: Face-centered cubic Daidzein_Au NPs with an average size of 25.78 nm and a negative surface charge were successfully synthesized. The minimum inhibitory concentration (MIC) of Daidzein_Au NPs against the tested CRE strains was 8– 16 μg/mL, and they exerted a good antimicrobial effect during the dynamic killing process. In vivo experiments showed that Daidzein_Au NPs can significantly enhance the survival rate (100%) and reduce the colony load of ascites in mice (P < 0.05). Furthermore, Daidzein_Au NPs destroyed the permeability of bacterial cell membranes, increased the production of ROS (P < 0.05), and affected the metabolism of CRE strains to play a role in killing.Conclusion: Daidzein_Au NPs exhibit excellent antibacterial activity and are expected to become a promising solution to the threats posed by CRE strains. Keywords: Daidzein, gold nanoparticles, carbapenem-resistant Enterobacteriaceae, antibacterial mechanism